Model Informed Development of VRC01 in Newborn Infants Using a Population Pharmacokinetics Approach. Issue 1 (3rd October 2020) - Li, Jerry; Nikanjam, Mina; Cunningham, Coleen K.; McFarland, Elizabeth J.; Coates, Emily E.; Houser, Katherine V.; Lin, Bob C.; McDermott, Adrian B.; Flach, Britta; Gama, Lucio; Koup, Richard A.; Graham, Barney S.; et al.
Abstract : VRC01 is a first‐in‐class, potent, broadly neutralizing antibody that targets the CD4 binding site of gp120 on HIV‐1 viruses, and is under development as a novel HIV therapeutic. This study utilized population pharmacokinetic (PK) modeling to characterize VRC01 PK to guide dosing selection for ongoing phase II clinical trials in pediatric patients. Combining VRC01 PK data from 3 adult and 1 infant clinical trials, a total of 1, 475 VRC01 serum concentrations from 100 participants were used in the analysis (40 infants and 60 adults). VRC01 was administered either i.v. or s.c. (1–40 mg/kg). All infants received s.c. doses as compared with 13% s.c. and 87% i.v. in adults. The data were well‐described by a two‐compartment model. Clearance was 37% higher in adults with HIV infection and 83% lower in infants than adults. Subcutaneous bioavailability was 55% in adults. Rapid absorption was seen in infants indicating therapeutic levels could be achieved quickly. Monte Carlo simulations were used to determine optimal dosing and demonstrated 40 mg/kg s.c. at weeks 0, 2, 6, and 10 would maintain VRC01 levels at the suppressive target concentration of 50 μg/mL for the first 14 weeks of life in infants. The current analysis provides new insight into differences in monoclonal antibody PK between infants and adults and demonstrates the utility of a population PK approach in informing drug development for infant populations.